Fitness landscapes and distance metrics for model-based leakage localization - Steffelbauer, David B.; Fuchs-Hanusch, Daniela (Conference on Control and Fault-Tolerant Systems (Print), 2016)
This paper aims to investigate the effect of distance metrics on the fitness landscape for model-based leakage localization and its impact on the performance of the differential evolution optimization algorithm applied to a theoretical water distribution network from literature.